Psychotherapy in Siberia: prospection from the past - V. Ya. Semke (Бюллетень сибирской медицины, 2003)
In the article there are cited the historical data on psychotherapy development in the east region of the country, mentioned the main stages of psychotherapeutic service perfection in Siberia, outlined the ways of organizational, clinical-dynamic and preventive approaches for the nearest and further prospects of scientific and practical psychotherapy making as a base of creation of a healthy and harmonious individual and social relations.